Dairy Cattle, a Potential Reservoir of Human Campylobacteriosis: Epidemiological and Molecular Characterization of Campylobacter jejuni From Cattle Farms - An, Jae-Uk; Ho, Hungwui; Kim, Jonghyun; Kim, Woo-Hyun; Kim, Junhyung; Lee, Soomin; Mun, Seung-Hyun; Guk, Jae-Ho; Hong, Sahyun; Cho, Seongbeom (Frontiers in Microbiology, 2018)
Campylobacter jejuni is a major foodborne pathogen that is increasingly found worldwide and that is transmitted to humans through meat or dairy products. A detailed understanding of the prevalence and characteristics of C. jejuni in dairy cattle farms, which are likely to become sources of contamination, is imperative and is currently lacking. In this study, a total of 295 dairy cattle farm samples from 15 farms (24 visits) in Korea were collected. C. jejuni prevalence at the farm level was 60% (9/15) and at the animal level was 23.8% (68/266). Using the multivariable generalized estimating equation model based on farm-environmental factors, we estimated that a high density of cattle and average environmental temperature (7 days prior to sampling) below 24℃ affects the presence and survival of C. jejuni in the farm environment. Cattle isolates, together with C. jejuni from other sources (chicken and human), were genetically characterized based on analysis of 10 virulence and survival genes. A total of 19 virulence profile types were identified, with type 01 carrying eight genes (all except hcp and virB11) being the most prevalent. The prevalence of virB11 and hcp was significantly higher in isolates from cattle than in those from other sources (p < 0.05). Thus, C. jejuni isolated from dairy cattle carries a higher potential risk upon transmission to humans. Multilocus sequence typing of C. jejuni isolates from three different sources mainly clustered in the CC-21 and CC-48. Within the CC-21 and CC-48 clusters, cattle isolates shared an indistinguishable pattern with human isolates according to pulsed-field gel electrophoresis and flaA-restriction fragment length polymorphism typing. This suggests that CC-21 and CC-48 C. jejuni from dairy cattle are genetically related to clinical campylobacteriosis isolates. In conclusion, the farm environment influences the presence and survival of C. jejuni, which may play an important role in cycles of cattle re-infection, and dairy cattle represent potential reservoirs of human campylobacteriosis. Thus, environmental management practices could be implemented on cattle farms to reduce the shedding of C. jejuni from cattle, subsequently reducing the potential risk of the spread of cattle-derived C. jejuni to humans through the food chain.